“To Be or Not to Be?” The Effect of Supervisor-Supervisee Relations on Students’ Completion of Doctoral Studies - David, Omona Andrew (World Journal of Education, 2020)
This paper analyses the effect of supervisor-supervisee relations on students’ completion of doctoral studies. It argues that, whereas doctoral studies is student focused, the success of the student is hinged on their relations with research supervisors. Three type of relationships: cordial, conflictual and sandwich are highlighted as key determinants of student’s progress. The paper further argues that, whereas supervisors are usually blamed by students as major source of their non-completion, students’ factors also greatly contribute to their completion or non-completion. Hence, to limit attrition numbers of doctoral students, there is need to address negative supervisor-supervisee relational issues.
Keywords: supervisor, supervisee, relationship, student’s completion, doctoral studies